Synthesis and characterization of chitosan-based nanodelivery systems to enhance the anticancer effect of sorafenib drug in hepatocellular carcinoma and colorectal adenocarcinoma cells - Ruman, Umme (MDPI AG, 2022)
10.3390/nano11020497